Gut microbiota in acute leukemia: Current evidence and future directions - Zhou, Yao; Zhou, Chendan; Zhang, Aijun (Frontiers in Microbiology, 2022)
Gut microbiota includes a large number of microorganisms inhabiting the human gastrointestinal tract, which show a wide range of physiological functions, including digestion, metabolism, immunity, neural development, etc., and are considered to play an increasingly important role in health and disease. A large number of studies have shown that gut microbiota are closely associated with the onset and development of several diseases. In particular, the interaction between gut microbiota and cancer has recently attracted scholars' attention. Acute leukemia (AL) is a common hematologic malignancy, especially in children. Microbiota can affect hematopoietic function, and the effects of chemotherapy and immunotherapy on AL are noteworthy. The composition and diversity of gut microbiota are important factors that influence and predict the complications and prognosis of AL after chemotherapy or hematopoietic stem cell transplantation. Probiotics, prebiotics, fecal microbiota transplantation, and dietary regulation may reduce side effects of leukemia therapy, improve response to treatment, and improve prognosis. This review concentrated on the role of the gut microbiota in the onset and development of AL, the response and side effects of chemotherapy drugs, infection during treatment, and therapeutic efficacy. According to the characteristics of gut microbes, the applications and prospects of microbial preparations were discussed.